Roles of imprinted genes in neural stem cells - Hoffmann, Anke; Daniel, Guillaume; Schmidt-Edelkraut, Udo; Spengler, Dietmar (Epigenomics, 2014)
Imprinted genes and neural stem cells (NSC) play an important role in the developing and mature brain. A central theme of imprinted gene function in NSCs is cell survival and G1 arrest to control cell division, cell-cycle exit, migration and differentiation. Moreover, genomic imprinting can be epigenetically switched off at some genes to ensure stem cell quiescence and differentiation. At the genome scale, imprinted genes are organized in dynamic networks formed by interchromosomal interactions and transcriptional coregulation of imprinted and nonimprinted genes. Such multilayered networks may synchronize NSC activity with the demand from the niche resembling their roles in adjusting fetal size.
Gesehen am 26.10.2020